Review article: the role of eltrombopag and romiplostim as the thrombopoietin receptor agonist (tpo-ra) in treatment of idiopathic thrombocytopenic purpura (itp): what is tpo-ra, when tpo-ra is used and how to take tpo-ra? - Susanto, Jefri Pratama (Folia Medica Indonesiana, 2016)
Idiopathic thrombocytopenic purpura is a autoimmune disease characterized thrombocytopenia casued by excessive platelet destruction. However, both platelet destruction and reduced thrombopoietin level are occurred in some cases. Therefore, new management of ITP is emerged which target is to increase platelet production rate via eltrombopag or romiplostim as the thrombopoietin receptor agonist (TPO-RA). Eltrombopag is given orally while romiplostim is given subcutaneously or intravenously and dose adjustment is depend on platelet count. Both eltrombopag and romiplostim is indicated in minimal response glucocorticoid or intravenous immunoglobulin or splenetomy treatment.